Intergenerational Spillovers of Integration Policies: Evidence from Finland's Integration Plans - Hanna Pesola; Matti Sarvimäki (Institute of Labor Economics (IZA), 2022)
This paper shows that an integration policy aimed at unemployed adult immigrants generated positive spillovers for their children. Our research design builds on a discontinuity in the phase-in-rule of Finland's 1999 reform that introduced integration plans—a new approach for allocating unemployed immigrants to active labor market policies. We find that parents' integration plans substantially improved their children's grades and educational attainment and reduced their time out of employment, education, or training. Our examination of potential mechanisms suggests that integration plans increased parents' earnings, employment and exposure to native colleagues and pushed their children to better schools.
Keywords: J61; J68; J13; H53; 330; immigrants; integration policy; intergenerational effects